Management of sub-surface drip irrigation system and water saving in greenhouse - Abou Kheira A.A.; El Shafie A.H. (Water saving in Mediterranean agriculture and future research needs [Vol. 1], 2007)
The main objective of this study was to evaluate the suitability of sub-surface drip irrigation system at different depths of lateral line and at different spacing between drippers in greenhouse. For this goal, Hot-pepper plants (Calcium Annul) were transplanted under greenhouse and irrigated by sub-surface drip irrigation system with different burial depths (0,20 and 25 cm) and different distances between drippers (30 and 50 cm). The results demonstrated that water consumption of Hot-pepper, which was determined using the equation of class A pan evaporation during initial development and harvesting stages were 11.82 percent, 21.98 percent and 66.20 percent from the total water application for all treatments. For sub-surface drip lateral treatments, the average rate of growing was the highest at 20 cm depth of lateral line beneath the soil surface with both 30 cm and 50 cm of emitter spacing, where it was 13.95 and 13.94 cm/month respectively. In case of sub-surface drip laterals, the wider emitters the higher yield at all depths. On contrary, in case of surface drip laterals, the closer emitters the higher yield. The results recommended that the surface drip (zero depth) effective than 20 and 25 cm depths. Hence, the zero depth of lateral resulted in higher yield and more efficient of fertilizer uses. The highest gross margin (283.2 LE/treatment/season) was recorded by surface drip irrigation system (zero depth) with 50 cm spacing followed by 30 cm spacing (279.1 LE/treatment/season). This due to high value of total revenue and fruits yield, which affected by the distance between drippers and the depth of lateral line that effect on optimal moisture and salt distribution patterns and nutrient elements in the root zone.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)